2020
DOI: 10.1111/ans.16020
|View full text |Cite
|
Sign up to set email alerts
|

Early outcomes of emergency ventral hernia repair in a cohort of poorly optimized patients

Abstract: BackgroundStrangulated and obstructed ventral hernias require emergent repair to mitigate the risk of life‐threatening complications. Emergency ventral hernia repairs are associated with a higher rate of surgical complications and recurrence compared to elective repairs. The purpose of this study was to explore the impact of patient factors, hernia and operative characteristics on post‐operative outcomes in patients requiring emergency ventral hernia repairs.MethodsData were collected from a prospectively held… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 16 publications
2
0
1
Order By: Relevance
“…At multivariate analysis, a patient who had gut resection was 10.250 times more likely to have adverse outcomes compared to one that had no gut resection. Our ndings were in agreement with what was reported by Dissanayake (19) in Australia, where the need for bowel resection was associated with the occurrence of postoperative complications following emergency hernia surgery. Also in agreement with a study done in Egypt, which revealed that diabetes mellitus and bowel resection were signi cantly associated with adverse outcomes (25).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…At multivariate analysis, a patient who had gut resection was 10.250 times more likely to have adverse outcomes compared to one that had no gut resection. Our ndings were in agreement with what was reported by Dissanayake (19) in Australia, where the need for bowel resection was associated with the occurrence of postoperative complications following emergency hernia surgery. Also in agreement with a study done in Egypt, which revealed that diabetes mellitus and bowel resection were signi cantly associated with adverse outcomes (25).…”
Section: Discussionsupporting
confidence: 93%
“…Also, in a study conducted at Mulago national referral hospital in Uganda, among patients with femoral hernias, wound complications were seen in 30.8% of the participants and respiratory complications in 7.7% (18). Dissanayake (19) reported that complications were seen in 34% of the study participants in Australia with surgical site infection being the commonest while Mabula & Chalya (20) observed that the overall complication rate was 34.6% with surgical site infection being the commonest in Tanzania (20). All the above had ndings comparable to our study ndings.…”
Section: Discussionsupporting
confidence: 86%
“…Studies examining these types of ventral hernia repairs (umbilical/epigastric), have shown significantly higher mortality, reoperation, and readmission rates in the emergency setting, compared to elective hernia repair [15,17,18]. However, this study showed no significant differences in readmission or reoperation rates in patients undergoing emergency hernia repair, compared to elective.…”
Section: Discussioncontrasting
confidence: 62%
“…Inguinal hernia was the second most common type of hernia [13]. Other types of hernia are extremely rare in emergencies [14]. Only one case of Spigel's semi-lunar line hernia has been reported by the same authors [13].…”
Section: Discussionmentioning
confidence: 99%
“…Abdominal parietal hernia, the temporary or permanent exit of viscera through an anatomically pre-existing zone of weakness, is a frequent pathology in surgery [1]. It ranks second before vesicular lithiasis and after appendectomies in order of frequency [2]. Worldwide, the prevalence of strangulated hernias is estimated at 0.3% -2.9% [3].…”
Section: Introductionmentioning
confidence: 99%